Journal of International Humanitarian Action - Egger, Clara; Grzebyk, Patrycja; Heintze, Hans-Joachim.; Zwitter, Andrej; Olbrich, Philipp; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The Journal of International Humanitarian Action is an open access peer-reviewed journal for researchers, policymakers, practitioners, and anyone moved to understand contemporary challenges, reflect critically on practices, and engage at humanitarian action$1 (Bs leading edge. We welcome original academic and/or practice-informed contributions not only from scholars of international humanitarian law or practitioners of global nonprofit management, but also from myriad other areas spanning the social sciences and humanities and beyond. Relevant topics include, but are not limited to: humanitarian ethics humanitarian protection application of international humanitarian law (IHL) humanitarian programming, monitoring, and evaluation education and training of humanitarian aid workers the Humanitarian-Development-Security Nexus governance, organization, and evolution of humanitarian systems best practices and knowledge-sharing in humanitarian action politics of humanitarian aid humanitarian technology psychosocial elements of humanitarian action The journal regularly publishes special collections that can be proposed by guest editors and discuss in detail pressing questions of humanitarian action. Given the diversity of our readership, the editors seek submissions that transcend disciplinary and sectional divisions and promote rigorous and inclusive discourse around the challenges, problems, and practices of humanitarian action.s
Keywords: Humanitarian law; Human rights; Natural disasters; Demography; Population; Environment; International relations; International Humanitarian Law, Law of Armed Conflict; Human Rights; Natural Hazards; Population and Demography; Environmental Sciences; International Relations